Improved EMC design of wireless communication modules - Wu, Xianzhe (2017)
With the rapid development of communication information technology and electronic circuit technology, wireless communication modules combining the two kinds of the technologies, emerges and raises higher and higher requirements for component integration in terms of signal transmission rate, quality and the level of hardware. As a result, there are increasing number and more and more complex electromagnetic compatibility (EMC) problems of printed circuit board (PCB) of wireless communication modules. EMC refers to the capacity of different items of electrical equipment to work together without producing the electromagnetic interference influencing the normal operation of other devices in certain circumstances. How to study EMC of PCB for wireless communication modules through suitable methods is a study problem urgently to be solved. In the thesis, the specific study of EMC problems in PCB of wireless communication module is divided into study and EMC improvement design study because they are multifaceted and universal. In the first part, four models are established from the aspects of hole level, wire level, surface level and layer level of PCB for EMC analysis. Besides, the various factors that may affect the EMC of PCB is accurately analyzed. Some corresponding improvement opinions and suggestions are given, which have clear guiding significance for the EMC design of PCB with high frequency and mixed signals. In the second part, a kind of wireless communication chip CC2530 based on the ZigBee protocol in the market is selected and then a wireless communication module RF2530 is designed by centering on CC2530. Moreover, by combining with the EMC simulation data and conclusions in the former part, EMC improvement scheme is put forward. Besides, the EMC improvement design of RF2530 module is completed. A variety of analysis results of the EMC of RF2530 module before and after the improvement are compared and studied. It is concluded that EMC improvement scheme is practical and effective, and also indirectly proves that the analysis conclusions of EMC in the first part are valid and practicable and provides reference for the EMC analysis of PCB for wireless communication modules in future.